Sin pi/4*cos pi/4-sin pi/3*cos pi/6

slkncv slkncv    2   20.06.2020 11:54    2

Ответы
elinochek1 elinochek1  15.10.2020 14:31

sin(π/4)·cos(π/4) - sin(π/3)·cos(π/6) = I

\sin(\frac{\pi}{4}) = \frac{\sqrt{2}}{2}

\cos(\frac{\pi}{4}) = \frac{\sqrt{2}}{2}

\sin(\frac{\pi}{3}) = \frac{\sqrt{3}}{2}

\cos(\frac{\pi}{6}) = \frac{\sqrt{3}}{2}

I = \frac{\sqrt{2}}{2}\cdot\frac{\sqrt{2}}{2} -

- \frac{\sqrt{3}}{2}\cdot\frac{\sqrt{3}}{2} =

= \frac{2-3}{4} = -\frac{1}{4} = -0{,}25

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика